Isotopic niche of two coastal dolphins in a tropical marine area: specific and age class comparisons. (20th July 2015) - Di Beneditto, Ana Paula Madeira; Monteiro, Leandro Rabello
Abstract : Niche differentiation is the process by which species evolve different forms of resource use, and is used to explain the co-occurrence in a variety of habitats. The Bayesian framework of isotopic niche through quantitative niche metrics was applied to estimate and compare the niche breadth of two sympatric coastal dolphins Pontoporia blainvillei and Sotalia guianensis in a tropical marine area. The standard ellipse areas (SEAs) based on species were quite similar, but the SEAs based on age class showed that the matures' niche space is larger than the immatures' for both dolphins. A probabilistic comparison of SEAs indicated that specific differences are negligible compared with age class differences. Trophic level measures (δ 15 N range) indicated that the dolphins are comparable as top predators, and that immature specimens have a lower range of trophic levels than mature ones. In terms of variability of food sources (δ 13 C range), S. guianensis showed a larger value than P. blainvillei and mature specimens had larger δ 13 C range than immatures for both species. In general, P. blainvillei and S. guianensis were similar in the niche metrics, with SEAs overlap of 52.1 and 39.7%. The immature specimens showed reduced isotopic niche overlap between species (<3%). In conclusion, Pontoporia blainvillei and S. guianensis specimens have similar isotopic niches, but pronounced differences between immature and mature specimens, both intraspecific and interspecific. Isotopic niche and quantitative metrics along with previous data on stomach contents provide a strong representation of species niche and their relationships.